Cortical Excitability in Temporal Lobe Epilepsy with Bilateral Tonic-Clonic Seizures. (14th September 2021) - Hu, Lingli; Yin, Houmin; Yang, Linling; Chen, Cong; He, Chenmin; Chen, Yi; Zhu, Junming; Ding, Yao; Wang, Shuang; Ding, Meiping; Wang, Shan
ABSTRACT: Objective: We investigated motor cortical excitability (CE) in unilateral temporal lobe epilepsy (TLE) and its relationship to bilateral tonic-clonic seizure (BTCS) using paired-pulse transcranial magnetic stimulation (TMS). Methods: In this cross-sectional study, we enrolled 46 unilateral TLE patients and 16 age-and sex-matched healthy controls. Resting motor thresholds (RMT); short-interval intracortical inhibition (SICI, GABAA receptor-mediated); facilitation (ICF, glutamatergic-mediated) with interstimulus intervals (ISIs) of 2, 5, 10, and 15 ms; and long-interval intracortical inhibition (LICI, GABAB receptor-mediated) with ISIs of 200–400 ms were measured via paired-pulse TMS. Comparisons were made between controls and patients with TLE, and then among the TLE subgroups (no BTCS, infrequent BTCS and frequent BTCS subgroup). Results: Compared with controls, TLE patients had higher RMT, lower SICI and higher LICI in both hemispheres, and higher ICF in the ipsilateral hemisphere. In patients with frequent BTCS, cortical hyperexcitability in the ipsilateral hemisphere was found in a parameter-dependent manner (SICI decreased at a stimulation interval of 5 ms, and ICF increased at a stimulation interval of 15 ms) compared with patients with infrequent or no BTCS. Conclusions: Our results demonstrate that motor cortical hyper-excitability in the ipsilateral hemisphere underlies the epileptogenic network of patients with active BTCS, which is more extensive than those with infrequent or no BTCS.